X-ray determination of stresses in alumina scales on high temperature alloys - SARIOĞLU, CEVAT (SCIENCE REVIEWS 2000 LTD, 2000)
The resistance of alumina scales to cracking and spalling under the influence of growth and thermal stresses is a critical aspect of the environmental resistance of high temperature structural alloys, oxidation resistant coatings, and bond coats for thermal barrier coatings. However, the relative magnitudes of the stresses and their distribution are often not known. In this study several X-ray diffraction techniques are being used to measure the strains in alumina scales on a variety of high temperature alloys both during oxidation and after cooling to room temperature. The corresponding stresses are being calculated using appropriate elastic constants. The results include the observations that: (1) Growth stresses are higher in alumina formed on FeCrAl alloys as compared to that formed on nickel-base alloys, such as NiAl or single crystal superalloys (studies have not yet been performed on NiCrAl or CoCrAl alloys). (2) Yttrium additions to do not result in lower growth stresses in alumina scales on FeCrAl alloys even though the additions decrease the amount of lateral scale growth. (3) Growth stresses can be relaxed by plastic deformation of both the alloy and oxide. The implications of these results with regard to alumina adhesion are discussed.
Keywords: XRD; stresses; alumina scales; OXIDATION; OXIDE; GROWTH; YTTRIUM; CREEP; ADDITIONS; ADHERENCE; BEHAVIOR; LAYERS